Religious Tolerance In Communication Community Groups In Regency Donggala - Fadhlia, Fadhlia; Zainuddin, Sumarni; Fauzan, Ahmad; Melisa, Ade Putri; Jaya, I Kadek Yuda; Zahra, Siti (Jurnal Ilmu Sosial Mamangan, 2023)
Religion is belief man to His God. Every group public Which adhere to religion certain must Can show behavior positive to group religion Which other And so also on the contrary, as in the community in Parisan Agung Village. Religious differences require people to tolerate. Objective study that is For know And give description about Religious tolerance in community group communication in Donggala Regency. Draft theory used related with tolerance and communication group with focus on conversational boundary theory. Method study qualitative with technique taking informant use purposive. Technique collection data is interview deep (In-depth Interview) and observation direct. For technique analysis use Data Reduction, Presentation Data and Conclusion Drawing/Verification. The results of the study show that in Parisan Agung Village, Donggala Regency, there is a plurality of religions that must be maintained properly through tolerant behavior by utilizing good communication between fellow Muslims and Christians. Tolerance is applied by using polite, friendly messages, mutual respect, empathy and not being easily influenced by hate speech on social media or face to face. Examples of tolerant behavior that are applied are inviting and attending the celebration of Eid al-Fitr and Christmas, helping each other in building houses of worship, not questioning worship carried out by other religions and saying sorry physically and mentally and Merry Christmas. Furthermore, often meeting in a village activity, either at a wedding, thanksgiving event and so on, the meeting is carried out by greeting each other. In the communication process that occurs between religious communities in Parisan Agung Village, each community limits the way they speak, meaning only conveying positive messages, and not discussing negative things that are related to a particular religion. This form of tolerance is a form of maturity from the people of Parisan Agung Village, Donggala Regency in order to maintain harmonious, harmonious and peaceful relationships.